Education for Professional Engineering Practice. (June 2014) - Bramhall, Mike D.; Short, Chris
This paper reports on a funded collaborative large-scale curriculum innovation and enhancement project undertaken as part of a UK National Higher Education Science, Technology Engineering and Mathematics (STEM) programme. Its aim was to develop undergraduate curricula to teach appropriate skills for professional engineering practice more effectively. Sheffield Hallam University (SHU) led the project with Loughborough and London South Bank Universities as partners. Project advisers included Imperial College London and Coventry University. The four collaborative project objectives were to: develop an approach to interdisciplinary cross-year integration and professional team practice, project management, learning, teaching and assessment; develop cross-year student support systems to aid the above; develop the assessment of professional skills; and evaluate and disseminate the project outcomes to the wider STEM community. The activity allowed partners to trial and test a rounded implementation in each institution involving academic taught material, practical laboratory-based project work, together with an appropriate support structure for operation across a range of undergraduate courses.